Belowground induction by Delia radicum or phytohormones affect aboveground herbivore communities on field-grown broccoli - Pierre, Sandra P.; Dugravot, Sebastien; Hervé, Maxime R.; Hasan, Hany; Van Dam, Nicole M.; Cortesero, Anne Marie (Frontiers in Plant Science, 2013)
Induced plant defence in response to phytophagous insects is a well described phenomenon. However, so far little is known about the effect of induced plant responses on subsequently colonizing herbivores in the field. Broccoli plants were induced in the belowground compartment using (i) infestation by the root-herbivore Delia radicum, (ii) root application of jasmonic acid (JA) or (iii) root application of salicylic acid (SA). The abundance of D. radicum and six aboveground herbivores displaying contrasting levels of host specialisation were surveyed for five weeks. Our study showed that the response of herbivores was found to differ from one another, depending on the herbivore species, its degree of specialisation and the root treatment. The abundance of the root herbivore D. radicum and particularly the number of emerging adults was decreased by both phytohormone treatments, while the number of D. radicum eggs was increased on conspecific infested plants. The root infestation exhibited moderate effects on the aboveground community. The abundance of the aphid Brevicoryne brassicae was strongly increased on D. radicum infested plants, but the other species were not impacted. Root hormone applications exhibited a strong effect on the abundance of specialist foliar herbivores. A higher number of B. brassicae and Pieris brassicae and a lower number of Plutella xylostella were found on JA treated plants. On SA treated plants we observed a decrease of the abundance of B. brassicae, Pi. rapae and P. xylostella. Surprisingly, generalist species, Mamestra brassicae and Myzus persicae were not affected by root induction treatments. Finally, root treatments had no significant effect on either glucosinolate profiles of the heads or on plant quality parameters. These results are discussed from the perspective of below- aboveground interactions and adaptations of phytophagous insects to induced plant responses according to their trophic specialisation level.